Victor Hugo Raconté par Un Témoin de Sa Vie - Victor Hugo (1920)
"In the autobiographical notes which the poet dictated to his wife and which were published in 1863 under the title .. Victor Hugo raconté par un témoin de sa vie, a wholly apocryphal account of the origins of the Hugo family is given". (Encuclopaedia Britannica. v. 11, p. 868, 1963.) | V. 1. 1802-1818 – v. 2. 1817-1841 | 31
Source a verifier sur Internet Archive
Keywords: Victor Hugo